Systematic Literature Review (SLR): HOTS pada Kurikulum Matematika di Malaysia - Fathurrohman, Fani Laffanillah; Junaedi, Iwan; Mulyono, Mulyono (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2025)
Higher Order Thinking Skills (HOTS) are among the skills developed within the mathematics curriculum. This study aims to describe the role of HOTS in the Mathematics Curriculum in Malaysia. The research method employed a Systematic Literature Review (SLR) using data sources from journals published between 2019 and 2024, obtained from Google Scholar and Scopus. The results show that: (1) the Standard Curriculum for Secondary Schools (KSSM) in Mathematics has been redesigned and refined to equip students with theknowledge, skills, and values necessary to meet the demands of the 21st century and to develop individuals with mathematical thinking abilities, including Higher Order Thinking Skills (HOTS); and (2) HOTS are explicitly stated within the curriculum to enable teachers to integrate them into the teaching and learning process, thus stimulating structured and focused student thinking. These skills encompass the application of knowledge, abilities, and values for reasoning, reflecting, problem-solving, decision-making, innovating, and creating